2021
DOI: 10.1002/essoar.10506200.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Cancer Risk from Unregulated Polycyclic Aromatic Hydrocarbons

Abstract: including the URL of the record and the reason for the withdrawal request.Polycyclic aromatic hydrocarbons (PAHs) are a class of chemicals that contain multiple fused aromatic rings, and are emitted into the atmosphere as byproducts of burning organic matter (Keyte et al., 2013). Several PAHs have been identified as mutagenic or carcinogenic (Bostrom et al., 2002) and therefore have the potential to harm the health of humans (Hansen et al., 2007;Park & Park, 2009) and ecosystems (Gray, 2002). In the atmosphere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
1
2
1
Order By: Relevance
“…This suggests significant health risk associated with the inhalation of polycyclic aromatic compounds in these two Central European cities. This is consistent with a recent study showing that 70% of the global population breathes air which exceeds the safe threshold level, with higher risks in China, India, Central and Eastern Europe ( Kelly et al, 2021 ). The risks estimated in this study for both PAHs and NOPAHs are somewhat similar to those previously reported in several locations in China ( Bandowe et al, 2014 ; Wei et al, 2015a ), Porto, Florence or Athens ( Alves et al, 2017 ) but higher than those found at Langfang, China ( Zhao et al, 2018 ) or Grenoble, France ( Tomaz et al, 2016 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests significant health risk associated with the inhalation of polycyclic aromatic compounds in these two Central European cities. This is consistent with a recent study showing that 70% of the global population breathes air which exceeds the safe threshold level, with higher risks in China, India, Central and Eastern Europe ( Kelly et al, 2021 ). The risks estimated in this study for both PAHs and NOPAHs are somewhat similar to those previously reported in several locations in China ( Bandowe et al, 2014 ; Wei et al, 2015a ), Porto, Florence or Athens ( Alves et al, 2017 ) but higher than those found at Langfang, China ( Zhao et al, 2018 ) or Grenoble, France ( Tomaz et al, 2016 ).…”
Section: Resultssupporting
confidence: 93%
“…This is different than what has been found elsewhere (e.g. a higher contribution of NPAHs to the PAC carcinogenicity (3.5%) than to PAC mass (0.7%), Huang et al, 2014a ), and particularly in a recent study at the global level estimating that NPAHs alone contributed to 15–20% of the carcinogenic potential of PAH mixtures ( Kelly et al, 2021 ).…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…58 The regulations were changed for the following reasons: (1) even if the concentration of B[a]P is low in food, contamination with other PAHs may still be present and (2) B[a]P is a minor contributor to total cancer risk at around 11%. 59 Before introducing PAH2, PAH4, and PAH8 as more accurate markers, it is important to note that according to regulations, smoked molluscs, muscle meat of smoked fish, heat-treated meat products, cocoa butter, and chocolates are food commodities with high potential to be contaminated by B[a]P. The maximum allowable level of B[a]P is 5 μg/kg. Due to the contamination of PAHs in water, direct consumption of aquatic organisms could contribute to the intake of PAHs.…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
“…The lifetime average daily dose (LADD) and the incremental lifetime cancer risk (ILCR) of toxic PAH compounds are common parameters of health risk via the inhalation route proposed by many epidemiologically based models 4,7,[31][32][33][34][35] . In the present study, to calculate the public health risk due to long-term and continuous exposure to carcinogenic PAHs in this study, the following Eqs.…”
Section: Health Impact Analysismentioning
confidence: 99%